2008
DOI: 10.1577/m06-285.1
|View full text |Cite
|
Sign up to set email alerts
|

Drift Dynamics of Larval Pallid Sturgeon and Shovelnose Sturgeon in a Natural Side Channel of the Upper Missouri River, Montana

Abstract: The drift dynamics of larval shovelnose sturgeon Scaphirhynchus platorynchus (1, 2, 6, and 10 d posthatch (dph)) and pallid sturgeon S. albus (1, 2, 5, 9, 11, and 17 dph) were examined in a natural side channel of the Missouri River to quantify the vertical drift location of larvae in the water column, determine the drift velocity of larvae relative to water velocity, and simulate the cumulative distance (km) drifted by larvae during ontogenetic development. Larvae were released at the side‐channel inlet and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
161
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(173 citation statements)
references
References 23 publications
7
161
5
Order By: Relevance
“…Even during high water, these structures may limit age-0 sturgeon access. For example, the majority of free-embryo sturgeon drift is near the bottom (Braaten et al 2008(Braaten et al , 2010, thus, even when these inlet control structures are overtopped during high water, young sturgeon may not be capable of successfully drifting over these structures. Woodward and Rus (2011) found that chute inlet control structures limited the amount of Missouri River course-grained suspended sediment entering Upper Hamburg and Glovers Point chutes, demonstrating the potential barrier that these structures may pose to other objects drifting near the bottom, such as sturgeon larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Even during high water, these structures may limit age-0 sturgeon access. For example, the majority of free-embryo sturgeon drift is near the bottom (Braaten et al 2008(Braaten et al , 2010, thus, even when these inlet control structures are overtopped during high water, young sturgeon may not be capable of successfully drifting over these structures. Woodward and Rus (2011) found that chute inlet control structures limited the amount of Missouri River course-grained suspended sediment entering Upper Hamburg and Glovers Point chutes, demonstrating the potential barrier that these structures may pose to other objects drifting near the bottom, such as sturgeon larvae.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the larvae of long migratory, potamodromous sturgeon species feature a continuous drift over several days and hundreds of kilometres (see Online Resource). Drift distance and duration are highly variable among species, and may be genetically coded in order to reach distinct nursery habitats and to compensate for the long upstream migrations of the adults (D'Amours et al 2001;Kynard and Horgan 2002;Kynard et al 2007aKynard et al , 2007bBraaten et al 2008Braaten et al , 2012. Instead of a continuous downstream movement, the early dispersal of other potamodromous species potentially includes a sequence of drifting phases (primarily during night), interspersed with periods of inshore settlement in nursery habitats (primarily during day) (Carter et al 1986;Gadomski and Barfoot 1998).…”
Section: What Types Of Fishes Drift?mentioning
confidence: 99%
“…Mathematical models have been used to estimate drift distances of some sturgeon species by integrating flow velocity and empirical data on drift duration, drift mode and swimming height (Kynard et al 2007a;Braaten et al 2008Braaten et al , 2012, but these sorts of studies are rare. There is an urgent need for research regarding the drift distance of other fishes (Fig.…”
Section: An Integrated Approach To the Drift Of Early Life Stages Of mentioning
confidence: 99%
“…These values thus vary among females every simulation year. After settlement, the initial length (L larvaint ) of 15.6 mm TL (±0.84 SE) is assigned to larvae (Braaten et al, 2008) as L larvaint = 15.6 + 0.84RN, where RN is a random number drawn from the normal distribution. Initial total mass is calculated using structural mass based on a length-dependent function with the assumption that sturgeon initially have optimally allocated energy in storage tissue (see Growth submodel in Appendix A (Supplementary material) for the formulation).…”
Section: Input Datamentioning
confidence: 99%